Structure–Function Studies Using Deletion Mutants Identify Domains of gC1qR/p33 as Potential Therapeutic Targets for Vascular Permeability and Inflammation - Ghebrehiwet, Berhane; Jesty, Jolyon; Xu, Sulan; Vinayagasundaram, Rama; Vinayagasundaram, Uma; Ji, Yan; Valentino, Alisa; Hosszu, Kinga H.; Mathew, Sally; Joseph, Kusumam; Kaplan, Allen P.; Peerschke, Ellinor I. (Frontiers in Immunology, 2011)
The endothelial cell (EC) receptor complex for kininogen (HK) comprises gC1qR, cytokeratin 1, and urokinase-type plasminogen activator receptor (uPAR) and is essential for activation of the kinin system that leads to bradykinin (BK) generation. Of these, gC1qR/p33 constitutes a high affinity site for HK—the BK precursor—and is therefore critical for the assembly of the kinin-generating cascade. Previous studies have identified a putative HK site within the C-terminal domain (residues 204-218) of gC1qR recognized by mAb 74.5.2. In these studies, we used information from the crystal structure of gC1qR, to engineer several deletion (Δ) mutants and test their ability to bind and/or support BK generation. While deletion of residues 204-218 (gC1qRΔ204-218), showed significantly reduced binding to HK, BK generation was not affected when tested by a sensitive bradykinin immunoassay. In fact, all of the gC1qR deletion mutants supported BK generation with the exception of gC1qRΔ154-162 and a point mutation in which Trp 233 was substituted with Gly. Binding studies also identified the existence of two additional sites at residues 144-162 and 190-202. Moreover, binding of HK to a synthetic peptide 190-202 was inhibited by mAbs 48 and 83, but not by mAb 74.5.2. Since a single residue separates domains 190-202 and 204-218, they may be part of a highly stable HK binding pocket and therefore a potential target for drug design to prevent vascular permeability and inflammation.